Development of Allometric Biomass Models for Hevea brasiliensis Müll. Arg. Plantation of Bangladesh: A Non-Destructive Approach - Hossain, Mahmood; Saha, Chameli; Siddique, Mohammad Raqibul Hasan; Abdullah, S. M. Rubaiot; Islam, S.M. Zahirul; Mondol, Falgoonee Kumar; Iqbal, Md. Zaheer; Akhter, Mariam; Matieu, Henry (Indian Forester, 2021)
Hevea brasiliensis Müll. Arg. is exotic in Bangladesh and largescale plantation has been established under governmental and private sectors for the production of natural rubber to meet the domestic demand. This species can sequestrate higher carbon compared to other species due to its fast-growing nature. Further promotion of this species is expecting in near future for both the economic and environmental benefits as a mitigation measure of climate change consequences. Allometric biomass models are important to estimate the biomass and carbon stocking. A non-destructive method was adopted to derive the allometric biomass models for H. brasiliensis in Bangladesh. The stem volume of 583 individuals of H. brasiliensis trees and biomass expansion factor (BEF) were used to estimate the total above-ground biomass (TAGB). A total of four allometric equations with natural logarithm were tested to derive best-fit biomass models for stem and TAGB. While five models were tested to derive the model of Biomass Expansion Factor (BEF). BEF = 24.872 * D^-0.765 was selected as the best-fit model of BEF. However, allometric models for stem and total above-ground biomass were Ln (Stem biomass) = -2.476+ 1.655*Ln (D) + 0. 746*Ln (H) and Ln (TAGB) = 0.738 + 0.890*Ln(D) + 0.746*Ln(H) respectively. The best-fit TAGB model showed the highest efficiency in biomass estimation compared to commonly used regional, pan-tropical, and species-specific biomass models in terms of model prediction error (MPE), model efficiency (ME).